Propuesta de mejora en el control de tiempos del proceso de empaques y embalajes para la reducción de horas extras en la empresa Servientrega S.A. en Acopi Yumbo. - Tobar Villada, Liler (Universidad Antonio Nariño, 2022)
Below are the results obtained by implementing method engineering in the company SERVIENTREGA S.A.; after analyzing that the packaging process lacks the control of times in the elaboration of the technical packaging, light guacal and heavy guacal, and therefore there is no control in the generation of overtime by the logistics assistants of the process. It was possible to establish that the work rhythm of the collaborators was not adequate, which represents the generation of overtime. Through the development of this work, it was possible to demonstrate with the analysis of methods and the proposal for improvement in plant distribution can reduce significant times within the packaging area.